Estudo da carbonatação avançada em concretos contendo adições minerais - Pires , Plínio Ferreira (2016)
The carbonation phenomenon consists in a physicochemical process which reduces the alkalinity of concrete. Carbonation can destabilize the protective layer of the steel, leaving it susceptible to corrosion, which is one of the most significant and costly causes of deterioration in reinforced concrete. Accordingly, chemical analysis of the pore solution has been held for about 60 years, but few studies are focused on types of concrete containing mineral additions subjected to carbonation, due to the difficulty of obtaining the pore solution, given its structure densification under these conditions. Depending on the concrete composition, the natural carbonation process can take several years to present sufficient analyzable data, therefore, most of the studies on this topic use accelerated tests to simulate this phenomenon. However, even with full control of the laboratory environment, it is not possible to reproduce the randomness of the variables responsible for the degradation that occur in real situations. This study aims to evaluate the process of natural carbonation in 36 different types of concrete or analysis conditions, which cover a wide range of characteristics and properties of concrete that represent the various service situations of the structures, after about 14 years of exposure, in typical urban environment. The results are presented for types of concrete with and without mineral additions (silica fume, rice husk ash, metakaolin, fly ash and blast furnace slag); three water/binder (0.40, 0.55 and 0.70) and two curing conditions (dry-cured and moist-cured). The study was conducted by the application of simplified models of carbonation and statistical analysis on an extensive experimental database (over 2000 measurements) obtained by eight evaluations of carbonation carried at different ages, through 14 years of natural exposure prototypes of concrete beams. In addition, chemical analysis of pH, ionic strength and conductivity of the pore solution - obtained through innovative method - were conducted in both the carbonated layer and the non-carbonated layer of concrete. The results indicate that the empirically-analytical model proposed by Tuutti, has an excellent representativity of carbonated depth over time. The use of a coefficient of carbonation, from Tuutti’s model, calculated from early ages, can generate mistaken conclusions: underestimating the dry-cured concrete and overestimating the moist-cured concrete. In the overall analysis of the natural carbonation coefficients obtained by ANOVA showed that the water/binder ratio is the most significant factor, followed by curing type and, finally, the type of addition. The best performances as the carbonation are observed to the lower water/binder concretes, subjected to wet cure. Under the method used to obtain the pore solution, it was possible to compare the difference between the chemical properties of non-carbonated and carbonated layers of each type of concrete analyzed.